ELAZIĞ YÖRESİNDEKİ ELMALARDA GÖRÜLEN KARA LEKE (VENTURİA İNAEQUALİS (CKE.) WİNT.) HASTALIĞI ÜZERİNDE ARAŞTIRMALAR - IŞIK, ERKAN (Fırat Üniveristesi, 2003)
Master Thesis INVESTIGATIONS ON APPLE SCAB ( Venturia inaequalis (Cke) Wint) AROUND ELAZI? Erkan IŞIK Fırat University Graduate School of Natural and Applied Sciences Department of Biology 2003, Page: 21 The materials of this study were apple varieties which have been grown in Elazığ The proportion of diseases were 20-30% on the variaty of Starking fruits, 36-40% on leaves; 8-15% on Golden fruits, 4-10% on leaves; 50-55% on Hüryemez fruits, 54-60 on leaves; 0.5-0.9% on Amasya fruits, 0.4-0.6% on leaves. The variaty of Amasya was resistant to apple scab and the others were susceptible in this study. The fungus owerwinters as perithecium on fallen leaves. Development of the perithecium, asci, and ascospres proceeds very slowly throughout the late fall, winter and early spring. In addition it overwinters as conidiospores on stored apples, fallen apples and in between the scales of the buds. But the primary inoculum sources are ascospores wich are spread by wind and rain. Keywords: Scab, Venturia inaequalis, apple, Elazığ, disease II
Investigations on apple scab (Venturia inaequalis (Cke.) Wint.) around Elazığ
Keywords: Biyoloji; Biology